Pietro I di Russia e la tentazione del Protestantesimo (Stato, Chiese e pluralismo confessionale, 2018)
SOMMARIO: 1. L’infanzia di Pietro - 2. Il rione degli stranieri - 3. La Grande Ambasciata - 4. L’inizio delle riforme - 5. Pietro e il monachesimo - 6. Il manifesto sulla tolleranza religiosa - 7. Pietro e la religione - 8. La subordinazione della Chiesa - 9. Feofan Prokopovyč e il suo ruolo determinante - 10. L’abolizione del Patriarcato - 11. Il Santo Sinodo governante e la paralisi della Chiesa.The Protestant Influence on the Church Reform of Peter the GreatABSTRACT: Peter the Great first comes into contact with the outside world through long familiarity with the German Quarter, a fluctuating Muscovite community of foreigners with its Lutheran and Calvinist churches, and with subsequent and extensive travel in the Protestant Lands (1697-1698), where he has ample time to appraise the role of sovereign as head of the church. The relationship of the tsar to his church is paradoxical; on the one hand, it emanates laws contrary to the principles sanctioned by the Church's Councils and organizes blasphemous parodies with The All-Joking, All-Drunken Synod of Fools and Jesters; conversely, he imposes rigidly traditional religious behaviors on the military. Rejecting his role and duty as Servant of the Salvation of Souls, he assumes a secular stance: Protector of the wellbeing of the community, (Vsenarodnaja pol’za). This swerve subordinating Church to sovereign undergoes elaborate scrutiny by Feofan Prokopovyč, apologist and theologian with Protestant leanings, who, in light of the abolition of the Patriarchate and the institution of the Holy Synod, affirms the principle of cuius regio eius et religio, openly challenging the position of the locum tenens Stefan Javors’kyj.
Keywords: Diritto ecclesiastico (Storia del)